Isolation of Japanese encephalitis virus and a novel insect-specific flavivirus from mosquitoes collected in a cowshed in Japan - Kuwata, Ryusei; Sugiyama, Hiroki; Yonemitsu, Kenzo; Van Dung, Nguyen; Terada, Yutaka; Taniguchi, Masayasu; Shimoda, Hiroshi; Takano, Ai; Maeda, Ken (Archives of virology, 2015)
Cattle do not generally appear to develop severe viremia when infected with Japanese encephalitis virus (JEV), and they can be infected without showing clinical signs. However, two cattle in Japan recently died from JEV infection. In this study, we investigated the presence of different species of mosquitoes and flavivirus in a cowshed in the southwest region of Japan. In this cowshed, the two most common species of mosquitoes collected were Culex tritaeniorhynchus (including Culex pseudovishnui) and Anopheles sinensis. We performed virus isolation from the collected mosquitoes and obtained two flaviviruses: JEV and a novel insect-specific flavivirus, tentatively designated Yamadai flavivirus (YDFV). Phylogenetic analysis revealed that all three JEV isolates belonged to JEV genotype I and were closely related to a JEV strain that was isolated from the brains of cattle exhibiting neurological symptoms in Japan. Genetic characterization of YDFV revealed that the full genome RNA (10,863 nucleotides) showed homology with the Culex-associated insect-specific flaviviruses Quang Binh virus (79 % identity) and Yunnan Culex flavivirus (78 % identity), indicating that YDFV is a novel insect-specific flavivirus.